Developing Instructional Media Based on ICT for Fourth Grade Students - Nurul Afidah; Oktavia Ayu Kristanti; Hanifah Hanifah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
ABSTRACT The aim of this study is to develop ‘English Fun’ in English instruction for fourth grade students of MI Al Hidayah Pagotan Jombang. This product focused on some vocabularies such as fruit, part of body, vegetables, and animals. The researcher chooses the ADDIE model in developing the product. This model consists of five steps. Those are: (1) analyze, (2) design, (3) development, (4) implementation, and (5) evaluation.on develop phase, validation sheet was used to evaluate the quality of English Fun that was developed. Based on the data from the material expert validation sheet instrument above, the average of the overall aspect was 94% which means this product was “very good